EFFECT OF MYCOFIX +3 IN TOXICITY REDUCTION OF T-2 TOXIN IN QUAILS - A. Shareef (Mesopotamia Journal of Agriculture)
Sixty newly hatched unsexed brown local quail chicks were fed diets containing 4 ppm T-2 toxin singly or in combination with the mycofix+3.0 adsorbent at a rate of (0.25%) for a period of 42 days, to investigate their effects on performance and blood profile. Birds were randomly allotted to three groups of 20 each ( with two replicates), i.e., control, T-2, and T-2 +Mycofix+3. Significant (P≤0.05) reduction in quail performance was observed from the first week onwards in the toxin fed birds compared to other groups. Mortality reaches 25% in toxin fed group. Significant (P≤0.05) reduction in the relative weight of lymphoid organs and pancreas were noted , while there was an increase in the weight of liver, proventriculus and gizzard compared with control group. Significant (P ≤ 0.05) reduction in blood picture, differential lymphocytes count, triglycerides and alkaline phosphatase (ALP), and a significant (P≤0.05) increase in heterophils, glucose, serum enzymes Aspartate aminotrasferase (AST), Alanine aminotrasferase (ALT), and stress factor between control and toxin treated group was observed. Addition of mycofix+3.0 at a rate of (0.25%) was significantly (p≤0.05) improved performance, restored internal organ weights, and blood parameters to that of control. In conclusion, it was clear that the addition of mycofix is effective in averting the toxicity of T-2 toxin in quails. Key words Japanese quail - T2 toxin -mycofix+3–performance- blood parameters